Effects of Curing, Smoking and Their Combined Treatment on Quality of Buffalo Meat During Refrigerated Storage - Ahmad, S; Anzar, A; Srivastava, A K; Srivastava, P K (Journal of Agricultural Engineering, 2005)
The study was conducted to evaluate the effects of curing, smoking and their combined treatment on physicochemical (pH), microbiological (TPC), and sensory (colour, odour and texture) quality of raw buffalo meat (RBM) during refrigerated storage (0degree C -5degree C). Curing brought improvement in pH, reduced total plate count (TPC) and developed colour, odour and texture. Curing combined with smoking increased (PH) to 6.30 while it was 5.98 for RBM and reduced to log TPC/g 2.69, while it was 4.30 for RBM. Colour, odour and texture were also improved. Storage study indicated that pH of cured meat further improved and reached to a maximum value (2.25), while there was no further improvement in pH of smoked meat during storage. There was continuous and consistent fall in pH values of raw, cured, smoked and cured plus smoked meat samples until it reached the minimum values (5.11, 5.23 for cured samples, 5.24 and 5.21 for smoked samples and 5.37 and 5.25 for cured plus smoked samples) at 0 and -5 degree C storage temperature respectively. These samples spoiled after 40,35 and 45 days at 0 degree C and 55, 50 and 60 days at -5 degree C, respectively.